„Sprawa” – pojęcie definiowane w oparciu o art. 45 ust. 1 Konstytucji RP - Michalska, Justyna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The right to a fair trial is a fundamental guarantee of protecting the rights and freedoms of the individual. The political position and competences of the courts remain the best guarantor of respect for human rights and freedoms. Article 45 par. 1 The Constitution of the Republic of Poland states that everyone shall have the right to a fair and public hearing of his case, without undue delay, before a competent, impartial and independent court. The subjective scope of the right to a fair trial, which “everyone” is entitled to the right, but the subject scope creates some doubts. The subject scope is “case”. However, the “case” is not specified by the constitution, and each branch of law differently regulates the “case”. On the basis of the Constitution of the Republic of Poland, the “case” is autonomous. The term “case” includes not only civil, criminal and administrative cases in their legal sense, but also refers to the basic function of the courts, which is to the administration of justice.
Keywords: case; court; the right to a fair trial; The Constitution of the Republic of Poland